The Effect of Cesarean Delivery on Child Survival and Early Breastfeeding Practices: Global Data from 103 Provinces in the Eastern Mediterranean Region - Al-Jawaldeh, Ayoub; Abul-Fadl, Azza (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Early initiation of breastfeeding (EIBF) plays an important role in the reduction of infant mortality. Although Cesarean section (CS) can save lives it delays EIBF and thereby increases risk of mortality.Aim: To examine the relationship between CS and EIBF with child mortality.Methods: Data was recruited from recent demographic health surveys for 129 provinces of seven Eastern Mediterranean countries.  The data was analyzed for breastfeeding initiation (EBFI) rates in the first hour and the first day, feeding prelacteals, delivery by skilled birth attendant (SBA), and delivery by CS, also neonatal mortality (NMR), infant mortality rates (IMR) and under-five mortality rates (U5MR). Statistical analysis was done using Pearson correlation and descriptive statistics. The economic cost of unnecessary CS correlated to mortality rates and EBFI.Results: Overall CS was inversely associated with EBFI in the first hour after birth (r-0.2, P=0.1), intake of prelacteals (r-0.3, P=0.008) and NMR (r-0.3, P=0.1), IMR (r-0.4, P=0.0001), and U5MR (r-0.4, P=0.0001) at P40 was inversely correlated with mortality at P